2008
DOI: 10.1016/j.lfs.2008.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of the cardiovascular and metabolic complications of obesity in CD14 knockout mice

Abstract: Aims: Although toll-like receptors (TLR) are known to mediate the metabolic complications of obesity, the mechanisms underlying its activation remain largely unknown. The present study analyzed a model of dietinduced obesity in mice lacking the TLR4/TLR2 co-receptor CD14. Main methods: Six-week-old male mice lacking CD14 (n = 16) were allocated to either a control diet or a highfat high-simple carbohydrate diet (5.4 kcal/g; 35% fat; 35% sucrose), and compared with C57BL/6 (WT; n = 15) controls. After 12 weeks,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
52
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 39 publications
(41 reference statements)
3
52
1
5
Order By: Relevance
“…To clarify the mechanisms of ME-induced innate immunity activation, mice lacking TLR4 co-receptor CD14 were studied. We have shown that CD14 KO mice when exposed to a high-fat highsimple carbohydrate diet show attenuation in CV and metabolic complications of obesity compared with wildtype mice (Roncon-Albuquerque et al 2008). Moreover, when chronically injected with LPS, CD14 KO mice do not show body weight gain and increased visceral and subcutaneous adipose depots, as observed in wildtype animals (Cani et al 2007a).…”
Section: Me and Nutritional Statusmentioning
confidence: 81%
“…To clarify the mechanisms of ME-induced innate immunity activation, mice lacking TLR4 co-receptor CD14 were studied. We have shown that CD14 KO mice when exposed to a high-fat highsimple carbohydrate diet show attenuation in CV and metabolic complications of obesity compared with wildtype mice (Roncon-Albuquerque et al 2008). Moreover, when chronically injected with LPS, CD14 KO mice do not show body weight gain and increased visceral and subcutaneous adipose depots, as observed in wildtype animals (Cani et al 2007a).…”
Section: Me and Nutritional Statusmentioning
confidence: 81%
“…Leptin and insulin affect Na ϩ excretion (2, 52) and thus potentially affect the analysis of Na ϩ transporters. Several studies have found that C57BL/6 mice develop obesity-related hypertension after high fat feeding (35-60% energy from fat) from as early as 8 wk (37,45,54) as well as impaired renal salt handling and salt sensitivity (7). C57BL/6 mice fed a HFD develop progressive insulin resistance and provide a good model for studying obesity-related hyperinsulinemia (55).…”
mentioning
confidence: 99%
“…In knockout mice lacking CD14 there is less diet-induced obesity and macrophage accumulation in adipose tissue (Cani et al, 2007;Roncon-Albuquerque et al, 2008). CD 14 is a co-receptor with toll-like receptor 4 [TLR4] for activation of macrophages by lipopolysaccharide and by free fatty acids, which Fessler et al (2009) have postulated to be the link between obesity and inflammation.…”
Section: Cd14mentioning
confidence: 99%